RED-LISTED ETHNOMEDICINAL PLANTS: IDENTIFYING GEOGRAPHIC ”HOT SPOTS” OF CONSERVATION CONCERN - Williams, V.; Crouch, N. R.; Victor, J. E.; Dold, A. P. (African Journal of Traditional, Complementary and Alternative Medicines, 2009)
Exploitation and excessive harvesting is a determining factor in the extinction risk of plants harvested for the traditional medicininal trade. This concerns especially the species that are in high demand. Harvesting has led to notable declines in the abundance and distribution of several species, and has thereby increased their level of vulnerability to unsustainable harvesting and extinction. Approximately 321 medicinal plant species have been assessed according to the 2001 IUCN Red List criteria, and more than 800 species remain to be assessed (but are mostly not threatened). Of the 321 assessed taxa, about 40% (±123 species) are of conservation concern (i.e. have been listed as critically endangered, endangered, vulnerable, near-threatened and least concern-declining). At the distribution level of one quarter-degree grid square (QDS), there are very few areas of KwaZulu-Natal and Mpumalanga that don’t have threatened or near-threatened medicinal plants. Most of the critically endangered species occur in the Mpumalanga and Limpopo Provinces, and there is a trend towards more vulnerable species being restricted to a band along the eastern coastline of South Africa, whereas less vulnerable species extend from the coast to the interior. “Hot spots” (i.e. QDSs that have the highest number of threatened medicinal taxa) include the Barberton and Durban-Pietermaritzburg areas, as well as parts of northern KwaZulu-Natal and the Eastern Cape. Reasons for the observed distribution patterns are being discussed.